The effects of duration of mesenteric artery ligation to the ratio of TNF-α/IL-10 in a rat model of acute mesenteric ischemia (AMI) - Adeodatus Yuda Handaya; Vicky S. Budipramana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
The mortality rate of acute mesenteric ischemia (AMI) is high due to the delay in diagnosis.Determination of potent biomarker for early AMI is the key in reducing the mortality. As aproinflammatory cytokine, the level of TNF-α might be affected during the ischemia andreperfusion, with the prediction duration of 60-120 min. High TNF-α level may stimulatethe upregulation of IL-10 as an inhibitor of TNF-α. This provides a new opportunity forearly diagnosis of AMI by measuring the ratio between those two cytokines. The purposeof this study was to investigate the effect of duration of the mesenteric artery to theratio of TNF-α/IL-10 in a AMI rat model. This was an experimental study using Wistarrat. We performed mesenteric artery in 28 male rats to produce an AMI model, withligation duration of 0, 30, 60, 90, 120, 150, and 180 minutes. At the end of ligation,blood samples were taken for measurement of TNF-α and IL-10 level using ELISA. For themicroscopic examination of tissue necrosis, intestinal organ samples were taken and madeinto paraffin blocks and stained using Haematoxylin-Eosin. TNF-α increased in minute 120compared to other treatment groups (p<0.05). IL-10 increased in minute 180 comparedto control group (p<0.05). Microscopic examination showed that the duration of ligationaffects the structure and morphology of intestinal mucosa characterized by discolorationof organs along with increasing the ligation duration. Ligation of the superior mesentericartery was found to be significantly increased the TNF-α level and to be compensated byincreasing IL-10. It is assumed that when the IL-10 level, that has protective effect as aninhibitor, higher than TNF-α level as a proinflammatory cytokine on duration 150 minutes,it means no more inflammatory or cells is dead. Therefore TNF-α/IL-10 ratio can be usedas a biomarker candidate of prognosic factor management of AMI.